High dosage of zinc modulates T-cells in a time-dependent manner within porcine gut-associated lymphatic tissue. Issue 12 (28th December 2018) - Kreuzer-Redmer, Susanne; Arends, Danny; Schulte, Jasper N.; Karweina, Diana; Korkuc, Paula; Wöltje, Nadine; Hesse, Deike; Pieper, Robert; Gerdts, Volker; Zentek, Jürgen; Meurens, Francois; Brockmann, Gudrun A.
Abstract: Zn serves as a powerful feed additive to reduce post-weaning diarrhoea in pigs. However, the mechanisms responsible for Zn-associated effects on the adaptive immune responses following feeding of a very high dosage of Zn remain elusive. In this study, we examined the T-cell response in gut-associated lymphatic tissues of seventy-two weaned piglets. Piglets received diets with 57 mg Zn/kg (low Zn concentration, LZn), 164 mg Zn/kg (medium Zn concentration, MZn) or 2425 mg Zn/kg (high Zn concentration, HZn) mg Zn/kg feed for 1, 2 or 4 weeks. We observed that feeding the HZn diet for 1 week increased the level of activated T-helper cells (CD4 + and CD8 α dim ) compared with feeding MZn and LZn ( P <0·05). In addition, we observed higher transcript amounts of interferon γ and T-box 21 ( TBET ) in the HZn group compared with the MZn and LZn groups ( P <0·05). A gene set enrichment analysis revealed an over-representation of genes associated with 'cytokine signalling in immune system'. Remarkably, feeding of a very high Zn dosage led to a switch in the immune response after 2 weeks. We detected higher relative cell counts of CD4 + CD25 high regulatory T-helper cells ( P <0·05) and a higher expression of forkhead box P3 ( FOXP3 ) transcripts ( P <0·05). After 4 weeks of feeding a high-dosage Zn diet, the relative CD4 + T-cell count ( P <0·05) and the relative CD8 β + T-cell count ( P <0·1) were reduced compared with the MZn group. We hypothesise that after 1 week the cellular T-helper 1 response is switched on and after 2 weeks it is switched off, leading to decreased numbers of T-cells.